Safety and Security at the Edges of the State : Local Regulation in Papua New Guinea’s Urban Settlements - Craig, David (World Bank, Washington, DC, 2018)
Cities are key to reducing poverty and promoting shared prosperity in Papua New Guinea (PNG). Cities generally are sites for cultivating and fostering the accumulation of multiple forms of capital. In urban areas, these different kinds of capital can bring economic, social, and political benefits to national development. Nurturing all of these forms of capital and turning them into development outcomes require security and regulation. The social and economic regulation of informal urban settlements in PNG needs to be expressed territorially and spatially in residential neighborhoods, public spaces and amenities, and transport nodes and routes. Regulatory failure, on the other hand, can lead to communal disputes and escalating violence at all levels that pervert and destroy capital and threaten national stability. This report will describe, the chief institutions of local regulation that have taken distinctive forms: local committees and flexibly institutionalized leadership roles, all enacted through mediation and the spatial regulation of settlements and markets. This report focuses on the everyday institutional arrangements that regulate the safety and security of PNG’s urban settlements in relation to people and places where the reach of formal authorities is limited, dysfunctional, and or lacks legitimacy.